What is the coefficient of x 9 9 in the polynomial expansion below?
( x − 1 ) ( x − 2 ) ( x − 3 ) ⋯ ( x − 1 0 0 )
Note : This was taken from a 1984 Mathematics competition, pretty long time ago.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
We notice that when this polynomial is written in expanded form, we get: x 1 0 0 + b x 9 9 + . . . , where b is the coefficient of x 9 9 . Vieta's theorem states that the sum of the roots of this polynomial is equal to 1 − b . Because of the expanded form the problem was originally given in, we quickly see that the sum of roots is given by 1 + 2 + 3 + . . . + 1 0 0 = 2 1 0 0 ∗ ( 1 0 0 + 1 ) = 5 0 5 0 . Thus − b = 5 0 5 0 , and b = − 5 0 5 0
By Vieta's formula, we know that a 9 9 = − i = 1 ∑ 1 0 0 x i = − n = 1 ∑ 1 0 0 n = − 2 1 0 0 ( 1 0 1 ) = − 5 0 5 0 , where x i are the roots (we can ignore a 1 0 0 since it is a monic polynomial).
yeah @jake Lai nice solution!
Problem Loading...
Note Loading...
Set Loading...
If you don't know any formulas you can solve this in the following way:
First expand ( x − 1 ) ∗ ( x − 2 ) ∗ ( x − 3 ) ... to find out that this becomes: x 3 − 6 x 2 + . . . In this case, the coefficient of the second highest power of x (that is, x 2 ) is − 1 − 2 − 3 = − 6 Therefore we can assume that the value of the coefficient of the second highest power of x (wich I will call A ) in a polynomial expansion with the form ( x − a 1 ) ∗ ( x − a 2 ) ∗ . . . ∗ ( x − a n ) = x n − A x n − 1 + . . . is simply the sum of all the terms not dependent on x in the parenthesis: A = − a 1 − a 2 − . . . − a n In the case of this problem, the terms a 1 , a 2 , a 3 . . . a 1 0 0 are equal to − 1 , − 2 , − 3 , . . . , − 1 0 0 . This is a arithmetic series with d = − 1 and a 1 = − 1 .
Using the formula to calculate this arithmetic series results in: A = 2 − n ∗ ( a 1 + a n ) = 2 − 1 0 0 ∗ ( − 1 − 1 0 0 ) A = − 5 0 5 0